Case Report: Severe acute pancreatitis accompanied by gastric mucosal exfoliation hemorrhage: clinical alerts and novel insights - Yanquan Liu; Hehui Zhang; Minjuan Zeng; Jian Luo; Yun Lai; He Huang; Qinglin Xu; Yuan Liu (Frontiers in Surgery)
Acute pancreatitis (AP), a condition marked by its swift progression, substantial individual discrepancies, and profound concealment, poses a formidable challenge. Within its severe form, known as severe acute pancreatitis (SAP), the disease assumes an even more prevalent status, often entwined with dire complications such as pancreatic abscess, circulatory shock, and the direst of all, multiple organ failure. Regrettably, the conjunction of SAP with gastric mucosal exfoliation culminating in massive hemorrhage remains an exceptionally rare phenomenon within the clinical realm. This study delves into a retrospective analysis of a singular, yet remarkable clinical case, where SAP's therapeutic odyssey unexpectedly led to gastric mucosa stripping and catastrophic gastrointestinal bleeding. This paper endeavors to unravel the diagnostic intricacies, explore the treatment modalities, and prognosticate the outcome, all with the ultimate aim of fostering a heightened clinical vigilance and fostering a novel, nuanced understanding of SAP's exceptional complications within the intensive care arena. Furthermore, this study aspires to serve as a beacon of reference, illuminating the path for clinical practitioners confronted with such elusive yet critical scenarios.